2019
DOI: 10.2134/jeq2018.06.0248
|View full text |Cite
|
Sign up to set email alerts
|

Biochar and Water Quality

Abstract: Biochar application is considered to be an emerging strategy to improve soil ecosystem services. However, implications of such application on water quality parameters have not been widely discussed. This paper synthesizes the state‐of‐the‐art research on biochar effects on water erosion, nitrate leaching, and other sources of water pollution. Literature indicates that in general, biochar application reduces runoff by 5 to 50% and soil loss by 11 to 78%, suggesting that it can be effective at reducing water ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 83 publications
(172 reference statements)
1
23
0
Order By: Relevance
“…Biochar contains a high C concentration (85.4% in this study) and often improves soil properties (Blanco‐Canqui, 2017). Limited or no effect of biochar in the present study may be due to the low (11.2 Mg ha −1 ) application rate (Blanco‐Canqui, 2019) to slightly alkaline soil. Previous studies found positive effects of biochar on degraded and coarse‐textured soils under application rate ≥50 Mg ha −1 (Chan et al., 2008; Kammann et al., 2011).…”
Section: Discussionmentioning
confidence: 59%
“…Biochar contains a high C concentration (85.4% in this study) and often improves soil properties (Blanco‐Canqui, 2017). Limited or no effect of biochar in the present study may be due to the low (11.2 Mg ha −1 ) application rate (Blanco‐Canqui, 2019) to slightly alkaline soil. Previous studies found positive effects of biochar on degraded and coarse‐textured soils under application rate ≥50 Mg ha −1 (Chan et al., 2008; Kammann et al., 2011).…”
Section: Discussionmentioning
confidence: 59%
“…Biochar represents a cheaper solution compared to other carbonaceous materials with very promising performances [136,137] due to the several interactions that occur on biochar particles, as summarized in Figure 3. Firstly, biochar has been used to remove persistent small organic molecules such as aromatics.…”
Section: Organic Pollutants Removalmentioning
confidence: 99%
“…According to three reviews (Blanco‐Canqui, 2019; Borchard et al, 2019; Liu et al, 2018), biochar application generally reduces nitrate leaching (Table 1). Biochar application can reduce nitrate leaching by imparting different physicochemical properties to soil although the exact mechanisms are still unclear.…”
Section: Nutrient Leachingmentioning
confidence: 99%
“…Yet, leaching of ammonium, P, and C also deserves consideration. A review found that biochar can have inconsistent effects on reducing leaching of ammonium, P, and C (Blanco‐Canqui, 2019), suggesting that biochar application may be more effective for reducing leaching of nitrates than other nutrients. Overall, biochar reduces nitrate leaching in most cases but can have variable effects on reducing leaching of other nutrients.…”
Section: Nutrient Leachingmentioning
confidence: 99%
See 1 more Smart Citation